INOVASI TAS RAMAH LINGKUNGAN DARI KULIT KERANG: PELATIHAN UNTUK MENINGKATKAN NILAI JUAL PRODUK UMKM - Surni, Surni; Agustina, Wa Ode (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study examines the innovation of eco-friendly bags made from seashell waste as an effort to enhance the economic value of SMEs in coastal areas, particularly in Wakatobi. The abundance of seashell waste, which often causes environmental problems, has the potential to be transformed into high-value aesthetic products through proper training and creative processing. The research focuses on (1) the process of converting seashell waste into marketable bag products, (2) training methods to improve the skills of SME artisans in design and sustainable production techniques, and (3) digital marketing strategies to expand market reach. Using a participatory action research approach, this program involves local artisans in Wakatobi through workshops on material selection, product design, and eco-friendly finishing techniques. The results show that this innovation not only increases the selling value of products by up to 40% but also reduces environmental pollution while creating new job opportunities. This study contributes to the development of sustainable creative industries in coastal communities by optimizing local resources.